„To jest wielki człowiek! A jaki skromny!” Uczłowieczony wizerunek Lenina w opowiadaniach - Goszczyńska, Monika (Przegląd Rusycystyczny, 2014)
Monika Goszczyńska Uniwersytet Mikołaja Kopernika, Toruń, Poland mm.goszczynska@gmail.com «ЭТО БОЛЬШОЙ ЧЕЛОВЕК! И КАКОЙ СКРОМНЫЙ!» — ГУМАНИЗИРОВАННЫЙ ОБРАЗ ЛЕНИНА В РАССКАЗАХ Резюме В последнее время среди представителей различных дисциплин, особенно культур-ных антропологов и филологов, можно заметить повышенный интерес к культу Ленина. Однако большинство авторов доступных исследований рассматривает социально-политические условия этого явления. В то время авторы уделяют мало внимания литературному воплощению Ленина, на которое безусловно стоит обратить внимание. Основной целью данного исследования является филологический анализ рассказов о Ленинне. В частности, обсуждаются черты характера Ленина в рассказах, используемые литературные, лингвистические и стилистические конвенций, а также функции этих произведений. „THIS IS A GREAT MAN! AND SO MODEST!” — THE HUMANIZED IMAGE OF LENIN IN SHORT STORIES Summary Recently, representatives of different disciplines, especially cultural anthropologists and philologists, take an active interest in the cult of Lenin. However, most of the available studies usually concern the socio-political conditions of this phenomenon. The authors devote little attention to the literary incarnation of Lenin, which is definitely worth taking a separate discussion. Therefore, the primary aim of this paper is to analyze the stories about Lenin from the philological perspective. In particular, there will be discussed the features, which have been blessed with their hero, as used literary, linguistic and stylistic conventions, and the functions of these works.